2004
DOI: 10.1214/088342304000000189
|View full text |Cite
|
Sign up to set email alerts
|

The Reverend Thomas Bayes, FRS: A Biography to Celebrate the Tercentenary of His Birth

Abstract: Thomas Bayes, from whom Bayes theorem takes its name, was probably born in 1701, so the year 2001 marked the 300th anniversary of his birth. This biography was written to celebrate this anniversary. The current sketch of his life includes his family background and education, as well as his scientific and theological work. In contrast to some, but not all, biographies of Bayes, the current biography is an attempt to cover areas beyond Bayes' scientific work. When commenting on the writing of scientific biograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 60 publications
0
26
0
1
Order By: Relevance
“…It seems more likely that Bayes' interest in the problem of inverse probability came from his readings of Newton's work on the causes of gravity, or as an answer to Hume's philosophical essay (Bellhouse, 2004;McGrayne, 2012;Stigler, 2013). 2 The political or critical nature of ANT has been debated in recent years in organization theory, notably by Whittle and Spicer (2008), who argued that early ANT work did not focus sufficiently on politics and power.…”
Section: En D N Otesmentioning
confidence: 99%
“…It seems more likely that Bayes' interest in the problem of inverse probability came from his readings of Newton's work on the causes of gravity, or as an answer to Hume's philosophical essay (Bellhouse, 2004;McGrayne, 2012;Stigler, 2013). 2 The political or critical nature of ANT has been debated in recent years in organization theory, notably by Whittle and Spicer (2008), who argued that early ANT work did not focus sufficiently on politics and power.…”
Section: En D N Otesmentioning
confidence: 99%
“…First, there is a wonderful paper by David Bellhouse (2003) [2]. Bellhouse has long been interested in Bayes and uncovered the manuscripts in the Stanhope collection.…”
Section: In Search Of Bayesmentioning
confidence: 99%
“…For example, Barnard (1958) suggested that Bayes had learned his mathematics, and implicitly probability, from de Moivre, who gave lectures or lessons in a London coffee house. This conjecture was made before it was discovered that Bayes had attended the University of Edinburgh (see, for example, Dale, 1991, andBellhouse, 2002) and had studied mathematics with James Gregory, nephew of the more eminent mathematician of the same name, in the early 1720s. Stigler (1986) more reasonably has argued that Bayes became interested in probability after reading Simpson (1755), after which he provided comments on Simpson's paper to John Canton.…”
Section: Bayes's Interest In Probabilitymentioning
confidence: 99%
“…Like his work in probability, his only publication in this area was published posthumously (Bayes, 1763b). Several biographies or biographical sketches of Bayes have been written, the most recent being Bellhouse (2002).…”
Section: Introductionmentioning
confidence: 99%